Preparation method of elastic silica composite aerogel material and application thereof

CN118206356BActive Publication Date: 2026-10-09DONGHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410419788.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2026-10-09
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

然而,通过普通溶液聚合方式所制备的有机-无机复合气凝胶,由于聚合物与无机物之间缺少强的相互作用,聚合物和无机物易形成相互独立的网络,导致所制备的有机-无机复合气凝胶无法充分发挥聚合物和无机物的各自优势

Benefits of technology

[0012] 1. This invention utilizes a freeze polymerization method, taking advantage of the confinement effect of ice crystals, to enable the in-situ chemical growth of silica nanoparticles onto the surface of cellulose nanofibers, obtaining cellulose nanofiber-silica core-shell aerogel units, which are then assembled to form an elastic silica composite aerogel material. Because the cellulose surface is uniformly coated with silica, the prepared aerogel exhibits excellent high-temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118206356B_ABST
    Figure CN118206356B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of elastic silica composite aerogel preparation method and its application, the composite aerogel is first by freeze polymerization, make sodium silicate in situ polymerization on cellulose nanofiber surface, after freeze casting and freeze drying, obtain immediately. Freeze polymerization utilizes ice crystal limit domain to make that silica nanoparticles can controllable growth on cellulose nanofiber surface. This with cellulose nanofiber as core, silica as shell's core-shell base unit structure can effectively improve the high-temperature performance and mechanical elasticity of the prepared composite aerogel, so that it can satisfy the thermal management application demand in extreme high temperature and complex environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of composite aerogel preparation, and specifically relates to a method for preparing and applying an elastic silica composite aerogel material. Background Technology

[0002] The development of thermal insulation materials is of great significance for improving energy efficiency and achieving energy conservation and emission reduction. Therefore, the development of new thermal insulation materials has become a key research focus in the field of materials science. Aerogels are a type of three-dimensional porous material with a spatial network structure. They possess ultra-high porosity (>80%) and extremely low thermal conductivity (0.01-0.03 W m K⁻¹). Compared to the previous generation of thermal insulation materials, their thermal conductivity can be reduced by about 2-3 orders of magnitude, thus holding the promise of replacing traditional thermal insulation materials in fields such as construction, industry, and aerospace. However, inorganic aerogels generally suffer from brittleness and cannot be molded into large blocks, while polymer aerogels cannot withstand high temperatures. Therefore, neither can meet the thermal insulation application requirements in extreme high-temperature and complex environments. Thus, how to prepare organic-inorganic composite aerogels and fully utilize the respective advantages of polymers and inorganic materials is an important issue in the field of thermal insulation.

[0003] Currently, common methods for preparing composite aerogels include physical blending and chemical growth. Chinese patent document CN108484962A discloses a method for preparing cellulose composite aerogels from waste paper. This invention uses cellulose from waste paper as a polymer base and carbon-based nanoparticles as a composite filler for physical blending to prepare composite aerogels. While this simple blending method can improve the mechanical properties of the aerogel to some extent, the significant polarity difference between the nanofiller and the polymer easily leads to localized inhomogeneities during the mixing process, thus affecting the overall mechanical, temperature resistance, and thermal insulation properties of the prepared composite aerogel.

[0004] In-situ chemical growth of inorganic nanoparticles within a polymer matrix can significantly improve the overall uniformity of the material. However, organic-inorganic composite aerogels prepared via conventional solution polymerization often fail to fully utilize the advantages of both polymers and inorganic materials due to the lack of strong interactions between them. This results in the polymers and inorganic materials forming independent networks. Therefore, efficiently combining polymers and inorganic materials to prepare high-performance organic-inorganic composite aerogels remains a significant challenge. Summary of the Invention

[0005] The technical problem to be solved by this invention is to provide a method for preparing an elastic silica composite aerogel material. This method overcomes the current difficulty in efficiently combining organic and inorganic components in composite aerogel materials. The prepared organic-inorganic core-shell nanofiber composite aerogel can simultaneously achieve excellent high-temperature resistance and mechanical elasticity. This invention uses cellulose nanofibers as the polymer matrix, and in-situ confined polymerization of silica nanoparticles is achieved through freeze polymerization. Following freeze casting and freeze drying processes, an elastic silica composite aerogel material with a core-shell basic structure is prepared.

[0006] A method for preparing an elastic silica composite aerogel material includes the following steps:

[0007] Step 1: Sodium silicate and cellulose nanofibers are placed in a solvent and ultrasonically dispersed to obtain a uniformly dispersed solution. Then, the pH value of the system is adjusted by an inducer to obtain the reaction precursor solution.

[0008] Step 2: The above mixed solution is rapidly frozen and then transferred to a specific low temperature for freeze polymerization for a period of time to obtain silica-cellulose nanofiber core-shell composite units;

[0009] Step 3: Assemble the silica-cellulose nanofiber core-shell composite unit obtained in Step 2 by freeze casting, and then remove the solvent by freeze drying to obtain organic-inorganic core-shell nanofiber composite aerogel.

[0010] The elastic silica composite aerogel material of this invention can be applied to thermal management applications in extreme high-temperature and complex environments. The elastic silica composite aerogel material for thermal management applications requires no additional processing and can be used directly.

[0011] Compared with the prior art, the present invention, employing the above-described technical solution, has the following advantages:

[0012] 1. This invention utilizes a freeze polymerization method, taking advantage of the confinement effect of ice crystals, to enable the in-situ chemical growth of silica nanoparticles onto the surface of cellulose nanofibers, obtaining cellulose nanofiber-silica core-shell aerogel units, which are then assembled to form an elastic silica composite aerogel material. Because the cellulose surface is uniformly coated with silica, the prepared aerogel exhibits excellent high-temperature resistance.

[0013] 2. The elastic silica composite aerogel material prepared in this invention has cellulose nanofibers inside its core-shell structure that can effectively overcome the problem of high brittleness of inorganic aerogels and greatly improve the mechanical flexibility and elasticity of the aerogel. Attached Figure Description

[0014] Figure 1 The images are scanning electron microscope (SEM) images of Example 1 at different freeze-polymerization times.

[0015] Figure 2 This is a scanning electron microscope image of Example 2.

[0016] Figure 3 This is a scanning electron microscope image of Example 3.

[0017] Figure 4 This is a scanning electron microscope image of Comparative Example 1.

[0018] Figure 5 The nitrogen adsorption-desorption curves and pore size distribution diagrams for Example 1 are shown.

[0019] Figure 6 This is the mechanical compressive stress-strain curve of Example 1.

[0020] Figure 7 The graph shows the thermal conductivity values ​​for Example 1 and Comparative Example 1.

[0021] Figure 8 This is an optical infrared thermal image of the high-temperature insulation in Example 1. Detailed Implementation

[0022] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0023] A method for preparing an elastic silica composite aerogel material includes the following steps:

[0024] Step 1: Sodium silicate and cellulose nanofibers are placed in a solvent and ultrasonically dispersed to obtain a uniformly dispersed solution. Then, the pH value of the system is adjusted by an inducer to obtain a reaction precursor solution.

[0025] The solvent used in step 1 is water, and the ultrasonic dispersion time is 10 minutes. The ratio of sodium silicate, cellulose nanofibers and water is 3-5:50-200:500-2000, and the pH of the solution after adjustment with an inducing agent is 7-11.

[0026] The inducing agent is hydrochloric acid, and the concentration of hydrochloric acid is 0.5-2 mol / L.

[0027] Step 2: The above mixed solution is rapidly frozen and then transferred to a specific low temperature for freeze polymerization for a period of time to obtain silica-cellulose nanofiber core-shell composite units.

[0028] The polymerization method used is freeze polymerization, and the mixed solution is rapidly frozen by liquid nitrogen freezing; the reaction temperature of freeze polymerization is -40 to 0℃, and the reaction time of freeze polymerization is 12 to 72 hours.

[0029] Step 3: Assemble the silica-cellulose nanofiber core-shell composite unit obtained in Step 2 by freeze casting, and then remove the solvent by freeze drying to obtain organic-inorganic core-shell nanofiber composite aerogel.

[0030] Before cryogenic casting, the silica-cellulose nanofiber core-shell composite unit obtained from polymerization in step 2 needs to be washed with water 3-5 times to remove unreacted monomers.

[0031] The freezing method used in cryogenic casting is liquid nitrogen freezing. The freeze-drying is carried out at a temperature of -50℃ and a pressure of 5Pa.

[0032] The elastic silica composite aerogel material prepared according to the present invention is used for thermal management in extreme temperatures and complex environments.

[0033] The raw materials used in this invention, sodium silicate (98%) and hydrochloric acid (37%), were purchased from Admas, and cellulose nanofibers (1% aqueous solution) were purchased from Flash Technology.

[0034] Example 1

[0035] Step 1: Dissolve 0.043g of cellulose nanofibers and 1g of sodium silicate in 10.5g of water, disperse in an ultrasonic machine for 10 minutes, and then adjust the pH of the system to 8-9 with 1mol / L hydrochloric acid.

[0036] Step 2: Pour the above mixed solution into a mold and freeze it rapidly with liquid nitrogen, then transfer it to a freezer at -20°C for 2, 6, 12 and 24 hours to react.

[0037] Step 3: Thaw the reaction system and wash it with water 3-5 times to remove unreacted monomers.

[0038] Step 4: Disperse the cleaned product in water with a solid content of 10%, freeze it with liquid nitrogen, and then transfer it to a freeze dryer at a temperature of -50℃ and a pressure of 5Pa for 48 hours to finally obtain elastic silica composite aerogel.

[0039] Figure 1The images shown are scanning electron microscope (SEM) images of Example 1 at different freeze-polymerization times. When the freeze-polymerization reaction time is short, only a small number of silica nanoparticles are present on the surface of the cellulose nanofibers. As the reaction time increases, the number of silica nanoparticles on the surface of the cellulose nanofibers gradually increases until they completely coat the cellulose nanofibers, forming a core-shell structure.

[0040] Figure 4 The image shown is a scanning electron microscope image of Comparative Example 1. Because the polymerization was carried out through solution polymerization, the polymerized silica nanoparticles grew randomly, with varying particle sizes and agglomeration.

[0041] Figure 5 The nitrogen adsorption-desorption curves and pore size distribution diagrams for Example 1 are shown. The results indicate that the composite aerogel of Example 1 has a high specific area, and the pore size distribution diagram shows that the pore size of the prepared composite aerogel material is mainly distributed below 20 nm.

[0042] Figure 6 The figure shows the mechanical compressive stress-strain curve of Example 1. The results show that Example 1 maintains good mechanical properties after 100 compressions at 30% compressive strain, while Comparative Example 1 has no compressive resilience.

[0043] Figure 7 The values ​​are the thermal conductivity values ​​for Example 1 and Comparative Example 1. The results show that the aerogel of Example 1 has a lower thermal conductivity than the aerogel of Comparative Example 1.

[0044] Figure 8 The image shows an optical infrared thermal image of the high-temperature insulation of Example 1. The results show that after being burned with a flame torch for 600 seconds, the prepared composite aerogel was not burned under the flame, and the temperature on the back of the aerogel remained very low, indicating that the composite aerogel has excellent high-temperature insulation performance.

[0045] Example 2

[0046] The preparation method of Example 1 was followed, except that the concentration of sodium silicate was changed to prepare Example 2.

[0047] Step 1: Dissolve 0.043g of cellulose nanofibers and 2g of sodium silicate in 10.5g of water, disperse in an ultrasonic machine for 10 minutes, and then adjust the pH of the system to 8-9 with 1mol / L hydrochloric acid.

[0048] Step 2: Pour the above mixed solution into a mold and freeze it rapidly with liquid nitrogen, then transfer it to a freezer at -20°C to allow it to react for 24 hours.

[0049] Step 3: Thaw the reaction system and wash it with water 3-5 times to remove unreacted monomers.

[0050] Step 4: Disperse the cleaned product in water with a solid content of 10%, freeze it with liquid nitrogen, and then transfer it to a freeze dryer at a temperature of -50℃ and a pressure of 5Pa for 48 hours to finally obtain elastic silica composite aerogel.

[0051] Figure 2 This is a scanning electron microscope image of Example 2. Compared to Example 1, due to the increased amount of sodium silicate, the silica nanoparticles in the microstructure of the prepared composite aerogel agglomerated locally.

[0052] Example 3

[0053] The preparation method of Example 1 was followed, except that the reaction temperature of the freeze polymerization was changed to obtain Example 3.

[0054] Step 1: Dissolve 0.043g of cellulose nanofibers and 1g of sodium silicate in 10.5g of water, disperse in an ultrasonic machine for 10 minutes, and then adjust the pH of the system to 8-9 with 1mol / L hydrochloric acid.

[0055] Step 2: Pour the above mixed solution into a mold and rapidly freeze it with liquid nitrogen, then transfer it to a freezer at -40°C to allow it to react for 24 hours.

[0056] Step 3: Thaw the reaction system and wash it with water 3-5 times to remove unreacted monomers.

[0057] Step 4: Disperse the cleaned product in water with a solid content of 10%, freeze it with liquid nitrogen, and then transfer it to a freeze dryer at a temperature of -50℃ and a pressure of 5Pa for 48 hours to finally obtain elastic silica composite aerogel.

[0058] Figure 3 This is a scanning electron microscope (SEM) image of Example 3. Compared to Example 1, due to the lower polymerization temperature, the size of the silica nanoparticles in Example 3 is reduced, and the continuity between particles is also decreased.

[0059] Comparative Example 1

[0060] Step 1: Dissolve 0.043g of cellulose nanofibers and 1g of sodium silicate in 10.5g of water, disperse in an ultrasonic machine for 10 minutes, and then adjust the pH of the system to 8-9 with 1mol / L hydrochloric acid.

[0061] Step 2: Pour the above mixed solution into a mold and then react at 25°C for 24 hours.

[0062] Step 3: Freeze the reaction product with liquid nitrogen, then transfer it to a freeze dryer at -50℃ and 5Pa for 48 hours to obtain the composite aerogel.

[0063] This invention relates to a method for preparing an elastic silica composite aerogel material and its application. The composite aerogel is first prepared by in-situ polymerization of sodium silicate on the surface of cellulose nanofibers via freeze polymerization, followed by freeze casting and freeze drying. Freeze polymerization utilizes ice crystal confinement to controllably grow silica nanoparticles on the surface of cellulose nanofibers. This core-shell structure, with cellulose nanofibers as the core and silica as the shell, effectively improves the high-temperature resistance and mechanical elasticity of the prepared composite aerogel, enabling it to meet the thermal management requirements of extreme high-temperature and complex environments.

Claims

1. A method for preparing an elastic silica composite aerogel material, characterized in that... Includes the following steps: Step 1: Sodium silicate and cellulose nanofibers are placed in a solvent and ultrasonically dispersed to obtain a uniformly dispersed solution. Then, the pH value of the system is adjusted by an inducer to obtain the reaction precursor solution. Step 2: The above mixed solution is rapidly frozen and then transferred to a specific low temperature for freeze polymerization for a period of time to obtain silica-cellulose nanofiber core-shell composite units; the polymerization method used is freeze polymerization, and the mixed solution is rapidly frozen by liquid nitrogen freezing; the reaction temperature of freeze polymerization is -40 to 0℃, and the freeze polymerization reaction time is 12 to 72 hours; Step 3: Assemble the silica-cellulose nanofiber core-shell composite unit obtained in Step 2 by freeze casting, and then remove the solvent by freeze drying to obtain organic-inorganic core-shell nanofiber composite aerogel. Before cryogenic casting, the silica-cellulose nanofiber core-shell composite unit obtained from polymerization in step 2 needs to be washed with water 3-5 times to remove unreacted monomers; the freezing method used for cryogenic casting is liquid nitrogen freezing.

2. The method for preparing the elastic silica composite aerogel material according to claim 1, characterized in that, The solvent used in step 1 is water, and the ultrasonic dispersion time is 10 minutes.

3. The method for preparing the elastic silica composite aerogel material according to claim 2, characterized in that, The ratio of sodium silicate, cellulose nanofibers and water is 3-5:50-200:500-2000, and the pH of the solution after adjustment with an inducing agent is 7-11.

4. The method for preparing the elastic silica composite aerogel material according to claim 2, characterized in that, The inducing agent is hydrochloric acid, and the concentration of hydrochloric acid is 0.5-2 mol / L.

5. The method for preparing the elastic silica composite aerogel material according to claim 1, characterized in that, The freeze-drying process in step 3 uses a temperature of -50℃ and a pressure of 5Pa.

6. The application of the elastic silica composite aerogel material obtained by the preparation method according to any one of claims 1-5 in thermal management under extreme temperatures and complex environments.

Citation Information

Patent Citations

  • Method for preparing cellulose composite aerogel from waste paper

    CN108484962A

  • In-situ preparation method of cellulose-silicon dioxide composite aerogel

    CN104448397A